THE SIGNIFICANCE OF THE MARKETING ORIENTATION CONCEPT IN THE NEW REALITIES (Economics and region, 2018)
The article presents an overview of the marketing orientation concept in the new realities. As a field of study marketing became in the early part of the twentieth century. The main focus of marketing courses in the beginning of 1950s and 1960s was on ‘how to do it’. In more recent times, focus has been turned to the side of an absolutely new direction and a new sense, namely, marketing has been announced as a philosophy and as a way of doing business.To be successful in business every company must be market and customer focused and heavily obsessed to marketing. Company activities should be focused on providing customer satisfaction rather than just simply producing products. This is not always as easy as it may first appear. Going on this way and doing an efficient job we can be ensure that value will be created and delivered at a profit to the company. And this is the ultimate goal of marketing.So the marketing concept begins with an attentive and well-defined market, manufacturers products / services dictated only by marketplace; conducts STP (segmentation, targeting, positioning) and focuses primarily on the results of customer needs; integrates all the marketing activities and efforts that may influence on customers. And as desired result it yields profits by creating positive relationships with the right customers at the right place and right time and based on customer value and satisfactionImplementing the marketing concept very often means more than just simply responding to customers’ desires and needs. Customer oriented companies looking for and research customers quite deeply to be able to learn their desires, lifestyles, behaviors, collect ideas and preferences.
Keywords: marketing concept; consumer value; sales concept; success of a company; management